Predicting Volleyball Serve-Reception - Paulo, Ana; Zaal, Frank T. J. M.; Fonseca, Sofia; Araújo, Duarte (Frontiers in Psychology, 2016)
Serve and serve-reception performance have predicted success in volleyball. Given the impact of serve-reception on the game, we aimed at understanding what it is in the serve and receiver’s actions that determines the selection of the type of pass used in serve-reception and its efficacy. Four high-level players received jump-float serves from four servers in two reception zones – zone 1 and 5. The ball and the receiver’s head were tracked with two video cameras, allowing 3D world-coordinates reconstruction. Logistic-regression models were used to predict the type of pass used (overhand or underhand) and serve-reception efficacy (error, out, or effective) from variables related with the serve kinematics and related with the receiver’s on-court positioning and movement. Receivers’ initial position was different when in zone 1 and 5. This influenced the serve-related variables as well as the type of pass used. Strong predictors of using an underhand rather than overhand pass were higher ball contact of the server, reception in zone 1, receiver’s initial position more to the back of the court and backward receiver movement. Receiver’s larger longitudinal displacements and an initial position more to the back of the court had a strong relationship with the decreasing of the serve-reception efficacy. Receivers’ positioning and movement were the factors with the largest impact on the type of pass used and the efficacy of the reception. Reception zone affected the variance in the ball’s kinematics (with the exception of the ball’s lateral displacement), as well as in the receivers’ positioning (distances from the net and from the target). Also the reception zone was associated with the type of pass used by the receiver but not with reception efficacy. Given volleyball’s rotation rule, the receiver needs to master receiving in the different reception zones; he/she needs to adapt to the diverse constraints of each zone to maintain performance efficacy. Thus, being able to flexibly vary positioning and passing, given local (zone) constraints, can yield an advantage in high-level volleyball serve-reception. Further research needs to consider other serve modes (e.g., power-jump serve) and a full-court context of performance to support the present study’s findings.